2016
DOI: 10.1039/c6nr05638e
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap modulation of MoS2monolayer by thermal annealing and quick cooling

Abstract: We developed a non-mechanical straining method to simultaneously modulate the bandgap and photoluminescence (PL) quantum efficiency of a synthesized molybdenum disulfide (MoS) monolayer on SiO, by vacuum annealing and subsequent quick cooling in ethanol. Influences of the thermal treatments at different temperatures from 100 °C to 600 °C on the PL and Raman spectra of the MoS monolayers are reported. A maximum PL peak intensity, twice that of the untreated counterparts under the same measurement conditions, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 48 publications
5
29
2
Order By: Relevance
“…When the temperature is higher than 200 °C, the intensity of the spectrum is no longer continue to be increased. Similarly, our previous work about the thermal treatments of MoS 2 thin film under temperatures from 100 °C to 600 °C obtained a maximum value of double PL peak intensity under 200 °C 20 . After 200 °C, it was found that the exciton peak intensity in MoS 2 sample is decreased linearly.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…When the temperature is higher than 200 °C, the intensity of the spectrum is no longer continue to be increased. Similarly, our previous work about the thermal treatments of MoS 2 thin film under temperatures from 100 °C to 600 °C obtained a maximum value of double PL peak intensity under 200 °C 20 . After 200 °C, it was found that the exciton peak intensity in MoS 2 sample is decreased linearly.…”
Section: Resultssupporting
confidence: 70%
“…It was also found that the PL intensity of WSe 2 ultrathin slab was increased three times under thermal treatment and annealing 19 . We previously reported that the quantum efficiency of MoS 2 ultrathin slab under thermal treatments can be increased twice of that under room temperature (RT) 20 .…”
Section: Introductionmentioning
confidence: 99%
“…PL enhancement by thermal treatment occurs at temperatures that are lower than the oxidation or decomposition temperature of MoS 2 with specific treatment durations. After the oxidation temperature or long process times, the PL intensity begins to decrease …”
Section: Adsorption Energy and Dissociation Energy Barrier Values Of mentioning
confidence: 99%
“…Because of the absence of bandgaps in graphene, recent research focused on searching of alternative 2D semiconductors . Monolayer transition metal dichalcogenide (TMDC), represented by MoS 2 and WSe 2 , have attracted extensive interests due to their intrinsic bandgaps and exciting features of indirect to direct bandgap transitions as the materials are thinned down to few‐layers . However, even though devices based on monolayer TMDCs have shown high on/off ratios and photosensitivities, their carrier mobilities are still much lower than graphene .…”
Section: Introductionmentioning
confidence: 99%